Hadis tentang Waswas Setan dalam Shalat: Kajian Ilmu Ma’anil Hadis - Umaira, Rahmi (Jurnal Riset Agama, 2022)
Worried in prayer, of course someone has experience. Examples when worship, someone has doubts in his prayers because of forgetting the number of prayers or other problems. Based on the case, it is in the hadith if someone feels disturbed in his prayers, to avoid the apostle to recommend bertaâ€™awudz accompanied by spitting to the left three times. But on the other hand, it is prohibited from moving in addition to the prayer movement because it can cancel prayer. Based on the hadith, the apostle recommends that bertaâ€™awudz be accompanied by spit to the left. Of course this is a problem in the prayer that it is prohibited from making movements other than the prayer movement, but on the other hand the prophet recommends that bertaâ€™awudz accompanied to spit to the left three times. So this is certainly more research can be done to deliver the understandingof the hadith. This study aims to discuss more in understanding the hadith on how to take refuge from worry in prayer with the approach to maâ€™anil hadith. This study uses a qualitative methods. The results of the study and discussion showed that the meaningÂ of word tafl (spit) in the hadith is not spitting as usual but the point is smal, which is blowing with a slight gusts of saliva. This is done if it does not disturb the sorrounding person. But if that does not allow it, it is enough to take refuge with God from the temptation of the damned setan without spitting, so that he does not harm the sorrounding person. The hadith which was the object of the status of shahih reviewed from sanad and its matan.